Mosque, Takya, Church and Schools in Badilis in the 16th and 17th Century - Mahmood, Salah M. S.; Younis, Majid M. (Humanities Journal of University of Zakho, 2017)
History cannot be study، read and write without the history of urbanization of humanities. In the light of it’s a part of history that answer’s many questions. This part of history is not taken into account many times correctly. It is noteworthy to say that this kind of neglect is inaccurate among the historian of the Middle East، the reason behind of this might be unstable of the region politically. Additionally، the conformational reasons، which ended up by violence many times. This was being a reason of taking into account political history and ignoring other parts of it، likewise، reading and researching of the political history are being a part of traditional، taking and using the same approach of writing history. This is on the other parts of historical account، ignoring the urbanization history، economy، and society. Hence، it’s necessary to take the urbanization history into account if it wants to show a clear picture، especially the urbanization history of Kurds in which they had great role in the human urbanization، meanwhile the ruling nation who had power on Kurdistan were always working to devastate its urbanization history with the aim of destroying Kurdish culture، intellectuality and literatures in addition to demolish of ancient Kurds in Kurdistan and their roles in constructing of urbanization. Certainly، Badilis is one of the most significant castle in the urbanization history of Kurdish in southern Kurdistan، which was one of the crucial emirate in the prior century، it has urbanization history that makes Kurds proud of it. As Badilis depicts its originality of its rich culture of Kurdish nation، likewise، it shows its powerful participation of constructing urbanization that shows its being among many nations at that time. Quite naturally، even many foreign visitors and Europeans brought it as an example of measuring its beauty، development of ideas and sciences.